Lost in Space? The spatial and scalar dimensions of organised crime in the Pacific. (10th August 2020) - Walton, Grant W.; Dinnen, Sinclair
Abstract : Two theoretical frameworks frame the spatial dimensions of organised crime. The first, which has shaped international responses to the problem, stresses the scalar and territorial nature of the problem; the second (and recently emerging) has drawn on network theories to suggest that organised crime is ascalar and operates through fluid relationships between people, places and things. We suggest that these viewpoints tend to bifurcate scalar and flat ontologies and argue that understanding and responding to organised crime requires engaging with theories of scale and networks simultaneously. We bring this theoretical insight to bear on a case study: we examine the way state power has shaped organised crime and responses to it across the Pacific. The case study highlights that responses to organised crime are by and large driven by scalar and state‐based responses, which have been shaped by political power. In contrast, organised crime constitutes networked relations that are significantly shaped by administrative and political scales. The paper argues that the disjuncture between the nature of responses to organised crime helps perpetuate the problem. It also highlights the advantages of greater dialogue between scalar and networked theories of organised crime.